Selenium capped monolayer NbSe2 for two‐dimensional superconductivity studies. Issue 12 (1st August 2016) - Onishi, Seita; Ugeda, Miguel M.; Zhang, Yi; Chen, Yi; Ojeda‐Aristizabal, Claudia; Ryu, Hyejin; Mo, Sung‐Kwan; Hussain, Zahid; Shen, Zhi‐Xun; Crommie, Michael F.; Zettl, Alex
Abstract : Superconductivity in monolayer niobium diselenide (NbSe2 ) on bilayer graphene is studied by electrical transport. Monolayer NbSe2 is grown on bilayer graphene by molecular beam epitaxy and capped with a selenium film to avoid degradation in air. The selenium capped samples have T C  = 1.9 K. In situ measurements down to 4 K in ultrahigh vacuum show that the effect of the selenium layer on the transport is negligible. The superconducting transition and upper critical fields in air exposed and selenium capped samples are compared. Schematic of monolayer NbSe2 /bilayer graphene with selenium capping layer and electrical contacts.